Synthesis, Characterization and Thermal Decomposition of p-Hydroxyacetophenone-aniline-formaldehyde terpolymeric Ligand - Dharkar, K.P.; Khamborkar, A.K.; Kalambe, A.B. (Asian Journal of Chemistry, 2011)
Terpolymeric ligand, p-hydroxyacetophenone-aniline-formaldehyde (PAF) has been synthesized by the condensation of p-hydroxyacetophenone and aniline with formaldehyde in the presence of an acid catalyst in 1:2:4 molar proportions of the reacting monomers. The characterization of terpolymeric ligand has been done on basis of elemental analysis, IR and 1H NMR. Thermal decomposition curve shows single decomposition step (270-495 ºC). The Sharp-Wentworth and Freeman-Carroll methods have been used to calculate thermal activation energy and thermal stability. Thermal activation energy (Ea) calculated by Sharp-Wentworth (20.89 KJ/mol) method and Freeman-Carroll (21.08 KJ/mol) method are in good agreement. Thermal decomposition of the terpolymeric ligand has been carried out to determine their mode of decomposition, the activation energy (Ea), order of reaction (n), frequency factor (Z), entropy change (DS), free energy change (DF) and apparent entropy change (S*) on basis of Freeman-Carroll method.